Gendang Pahang augmentation and technological symbiosis / Siti Khodijah Mohd Annuar and Mohd Kamal Sabran - Mohd Annuar, Siti Khodijah; Sabran, Mohd Kamal (2021)
Gendang Pahang is one of the traditional musical instruments that are less popular and known since modern music is more appealing to the generation today. Nowadays, there are many musical instruments that have been augmented to make it more interesting in this modern world; however, most of them are western or contemporary musical instruments while there are only a few studies that focused on augmented traditional musical instruments. This paper describes the development of Robotic Gendang Pahang, a technological innovation of traditional musical instruments using the original instruments. The aim of this paper is to describe the construction of the actuator control system and the mechanism of the beater to automatically hit the drums and gong without interfering with the original features of the instruments. This is to help introduce the traditional musical instruments to the public along with the real sound coming from the instruments itself without using any recording audio and real players. This paper also describes the prototype development using the prototyping method with few steps which are requirement gathering and analysis, preliminary design, building the prototype, initial evaluation, refining prototype and implementation. The results are discussed in terms of the design and performance analysis based on musical instruments’ robotic theory and future development